PENERAPAN ANALYTIC NETWORK PROCESS (ANP) PADA SISTEM PENDUKUNG KEPUTUSAN - Prind Triajeng Pungkasanti; Titis Handayani (Jurusan Teknologi Informasi Universitas Semarang, 2017)
Technology as a learning material will impact students impact in the future, in certain and details lesson material. Decission Support System teach how to solve the problems with algorythm methods application. One of them is Analytic Network Process (ANP). ANP is a complex methods with various stages in solving problems. ANP is difficult to understand in convensional way. Furthermore, this research aimed to solve the problems by create experimental tool called ANP application.